Inhibition of Glutaminyl Cyclases alleviates CCL2‐mediated inflammation of non‐alcoholic fatty liver disease in mice. Issue 3 (8th April 2013) - Cynis, Holger; Kehlen, Astrid; Haegele, Monique; Hoffmann, Torsten; Heiser, Ulrich; Fujii, Masato; Shibazaki, Yuichiro; Yoneyama, Hiroyuki; Schilling, Stephan; Demuth, Hans‐Ulrich
Summary Inflammation is an integral part of non‐alcoholic fatty liver disease (NAFLD), the most prevalent form of hepatic pathology found in the general population. In this context, recently we have examined the potential role of Glutaminyl Cyclases (QC and isoQC), and their inhibitors, in the maturation of chemokines, for example, monocyte chemoattractant protein 1 (MCP‐1, CCL2), to generate their bioactive conformation. Catalysis by isoQC leads to the formation of an N‐terminal pyroglutamate residue protecting CCL2 against degradation by aminopeptidases. This is of importance because truncated forms possess a reduced potential to attract immune cells. Since liver inflammation is characterized by the up‐regulation of different chemokine pathways, and within this CCL2 is known to be a prominent example, we hypothesised that application of QC/isoQC inhibitors may alleviate liver inflammation by destabilizing CCL2. Therefore, we investigated the role of QC/isoQC inhibition, in comparison with the angiotensin receptor blocker Telmisartan, during development of pathology in a mouse model of non‐alcoholic fatty liver disease. Application of a QC/isoQC inhibitor led to a significant reduction in circulating alanine aminotransferase and NAFLD activity score accompanied by an inhibitory effect on hepatocyte ballooning. Further analysis revealed a specific reduction of inflammation by decreasing the number of F4/80‐positive macrophages, which is in agreement with the proposed CCL2‐related mechanism of action of QC/isoQC inhibitors. Finally, QC/isoQC inhibitor application attenuated liver fibrosis as characterized by reduced collagen deposition in the liver parenchyma. Thus in conclusion, QC/isoQC inhibitors are a promising novel class of anti‐non‐alcoholic steatohepatitis drugs which have a comparable disease‐modifying effect to that of Telmisartan, which is probably mediated via specific interference with a comparable monocyte/macrophage infiltration that occurs under inflammatory conditions.